Home advantage and crowd attendance: evidence from rugby during the Covid 19 pandemic - Delbianco, F.; Fioravanti, F.; Tohmé, F. (Journal of Quantitative Analysis in Sports, 2023)
The COVID-19 pandemic forced almost all professional and amateur sports to be played without attending crowds. Thus, it induced a large-scale natural experiment on the impact of social pressure on decision making and behavior in sports fields. Using a data set of 1027 rugby union matches from 11 tournaments in 10 countries, we find that home teams have won less matches and their point difference decreased during the pandemic, shedding light on the impact of crowd attendance on the home advantage of sports teams.